Street vending challenges and opportunities: the case of women fish vendors in Fayoum - El-Azzazy, Mona (AUC Knowledge Fountain, 2019)
This exploratory research contributes to the documentation of the daily experiences of Egyptian women fish street vendors. The study explores the current situation of and prospects women fish vendors including daily constraints and potential for improvements. It informs about development interventions to improve their livelihoods; and finally, the hurdles and opportunities to optimize the benefits of interventions in a fishermen village in Fayoum governorate, Upper Egypt. Women face harassment and violence, the burden of performing paid and unpaid work, lack of access to credit, and the role of cultural norms in limiting women continuity in the business. This qualitative research attempts to narrow the literature gap identified in the studies of women street vendors in the Middle East and North Africa region, especially in the domain of fish vending in peri-urban and rural areas. The study findings demonstrate that saving groups have granted women entrepreneurs in the street vending business a great access to capital necessary to expand business and improve their livelihoods. The study concludes to the recommendation to continue investigating this important topic to inform policies that address women fish street vendors' constraints and enhance the wellbeing of people working in this sector. In this study, recommendations aim to improve the working conditions of food street vendors especially in fish business. Recognizing the work of women fish street vendors by official authorities is important, promoting social networking solutions is essential, encouraging women fish street vendors to lobbying allows them to gain more rights. All these recommendations would benefit vendors, their wider communities, and the national economy.